The WNK1–ERK5 route plays a pathophysiological role in ovarian cancer and limits therapeutic efficacy of trametinib. Issue 4 (8th April 2023) - Sánchez‐Fdez, Adrián; Matilla‐Almazán, Sofía; Montero, Juan Carlos; Del Carmen, Sofía; Abad, Mar; García‐Alonso, Sara; Bhattacharya, Somshuvra; Calar, Kristin; de la Puente, Pilar; Ocaña, Alberto; Pandiella, Atanasio; Esparís‐Ogando, Azucena
Abstract: Background: The dismal prognosis of advanced ovarian cancer calls for the development of novel therapies to improve disease outcome. In this regard, we set out to discover new molecular entities and to assess the preclinical effectiveness of their targeting. Methods: Cell lines, mice and human ovarian cancer samples were used. Proteome profiling of human phosphokinases, in silico genomic analyses, genetic (shRNA and CRISPR/Cas9) and pharmacological strategies as well as an ex vivo human preclinical model were performed. Results: We identified WNK1 as a highly phosphorylated protein in ovarian cancer and found that its activation or high expression had a negative impact on patients' survival. Genomic analyses showed amplification of WNK1 in human ovarian tumours. Mechanistically, we demonstrate that WNK1 exerted its action through the MEK5–ERK5 signalling module in ovarian cancer. Loss of function, genetic or pharmacological experiments, demonstrated anti‐proliferative and anti‐tumoural effects of the targeting of the WNK1–MEK5–ERK5 route. Additional studies showed that this pathway modulated the anti‐tumoural properties of the MEK1/2 inhibitor trametinib. Thus, treatment with trametinib activated the WNK1–MEK5–ERK5 route, raising the possibility that this effect may limit the therapeutic benefit of ERK1/2 targeting in ovarian cancer. Moreover, in different experimental settings, including an ex vivo patient‐derived model consisting of ovarian cancer cells cultured with autologous patient sera, we show that inhibition of WNK1 or MEK5 increased the anti‐proliferative and anti‐tumour efficacy of trametinib. Conclusions: The present study uncovers the participation of WNK1–MEK5–ERK5 axis in ovarian cancer pathophysiology, opening the possibility of acting on this pathway with therapeutic purposes. Another important finding of the present study was the activation of that signalling axis by trametinib, bypassing the anti‐tumoural efficacy of this drug. That fact should be considered in the context of the use of trametinib in ovarian cancer. Abstract : Activation of WNK1 associates to a worse ovarian cancer patient outcome. WNK1 signals cell proliferation through the ERK5 pathway. Trametinib provokes activation of the WNK1–ERK5 pathway. Combining trametinib with ERK5 route inhibitors may improve patients' outcome.